Evidence for Interspecific Brood Parasite Detection and Removal in Burying Beetles - Ashlee N. Smith; Mark C. Belk (Psyche: A Journal of Entomology)
We tested whether brood parasitism could be successful between two co-occurring species of burying beetles, Nicrophorus guttula and Nicrophorus marginatus, and whether these species exhibit an adaptive response to brood parasitism by detecting and removing parasites. We cross-fostered larvae between broods of the two species and created mixed-species broods to simulate the addition of brood parasites. Brood parasites survived in both species’ broods. Nicrophorus marginatus culled 86% of brood parasites compared to 56% of their own larvae, and N. guttula culled 50% of brood parasites compared to 22% of their own larvae. Additionally, N. guttula brood parasites were significantly smaller than N. guttula that were raised by N. guttula parents, but N. marginatus brood parasites were significantly larger than N. marginatus that were raised by N. marginatus parents. This paper provides the first evidence that burying beetles can discriminate between their own larvae and other species’ larvae. We suggest that brood parasitism may be the selective force responsible for this ability.